BIXS for tritium analysis with Ar gas and Al thin film as β-ray stopping layers and comparison with EBS. (September 2020) - Chen, H.; Ding, W.; An, Z.; Zhu, J.J.; Liu, M.T.; He, T.J.; Zhang, Z.
Abstract: β-ray induced X-ray spectrometry (BIXS) and elastic backscattering spectrometry (EBS) were utilized in this study for the tritium analysis of samples of tritium/deuterium-containing titanium films with thick Mo substrates. Using the BIXS method which incorporates Monte Carlo simulated data, we used Ar gas filler (BIXS-Ar) or placed Al film (BIXS-Al), respectively, between the sample and X-ray detector as β-ray stopping layers. Using the EBS method to confirm whether or not the tritium will volatilize under the impact of the proton beams, we conducted two measurements at the same point of the sample surfaces. A TiH film sample with thick Mo substrate was used in our EBS experiment to remove the influence of the Mo spectrum on the EBS experimental spectra of tritium/deuterium-containing samples. We well fit using the SIMNRA code the tritium and deuterium EBS spectra that were obtained by removing the Mo spectra. The tritium content and depth profiles in the titanium films were obtained via these different methods and the results were compared. It was found that the total tritium content measured using the EBS, BIXS-Al, and BIXS-Ar methods were in agreement within the experimental uncertainties, and the BIXS-Al method may be better at measuring the tritium depth profiles than the BIXS-Ar method. Highlights: We analyze tritium/deuterium-containing titanium film samples by BIXS and EBS. BIXS method is conducted by using Al thin film and Ar gas as stopping layer. BIXS-Al may be better than BIXS-Ar for obtaining tritium depth profile.